Vancomycin Versus Vancomycin Plus Rifampin for the Treatment of Acute Pulmonary Exacerbations of Cystic Fibrosis - Fusco, Nicholas M. (J Pediatr Pharmacol Ther, 2018)
OBJECTIVES: This study aimed to compare the change in pulmonary function in children and adolescents with cystic fibrosis (CF) who were infected with methicillin-resistant Staphylococcus aureus (MRSA) treated with either vancomycin (VAN) alone or vancomycin plus rifampin (VAN-RIF). METHODS: Included patients were ages 6 to 20 years; hospitalized for an acute pulmonary exacerbation (APE) of CF from May 1, 2012, to April 30, 2014; had a respiratory tract culture positive for MRSA within 1 month of index hospital admission; received at least 48 consecutive hours of VAN or VAN-RIF; and had admission and discharge pulmonary function tests. The primary end point was change in percent predicted forced expiratory volume in 1 second (FEV(1)). RESULTS: A total of 39 encounters met inclusion criteria: 24 in the VAN group (mean age 15.1 years) and 15 in the VAN-RIF group (mean age 13.7 years). There were no between-group differences in mean percent change in FEV(1) (32.6% ± 28.8% vs. 21.1% ± 12.1%; p = 0.091), mean percent change in forced vital capacity (22.6% ± 25.8% vs. 14% ± 9.4%; p = 0.127), or return to baseline FEV(1) (20 [83.3%] vs. 14 [93.3%] patients; p = 0.631). Median (IQR) length of stay (13 days [11–14 days] vs. 13 days [9–14 days]; p = 0.6) and median (IQR) time to readmission (82 days [43–129 days] vs. 147 days [78–219 days]; p = 0.2) were similar between the VAN and VAN-RIF groups, respectively. CONCLUSIONS: Vancomycin monotherapy appears to be adequate when treating APEs of CF in children and adolescents with moderate lung disease and high MRSA VAN minimum inhibitory concentrations. Therefore, the addition of RIF may be unnecessary; however, larger studies are needed to confirm these findings.